Military Spending and Economic Growth Dynamics in Iraq, 2004–2023: Dinamika Pengeluaran Militer dan Pertumbuhan Ekonomi di Irak, 2004–2023 - Huda Z. Miklif (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The relationship between military spending and economic growth has long been debated, with contrasting theoretical perspectives suggesting either positive stimulus effects or harmful crowding-out impacts. Specific Background: Iraq represents a critical case, as the post-2003 political and security instability substantially reshaped its public expenditure structure, with military allocations absorbing significant resources. Knowledge Gap: While prior studies have examined this relationship in Iraq, few have applied advanced econometric approaches across the extended period of 2004–2023, leaving uncertainty regarding short- versus long-term effects. Aims: This study analyzes the impact of military spending on Iraq’s GDP using the autoregressive distributed lag (ARDL) model to evaluate both short-run and long-run dynamics. Results: The findings reveal that military spending has only a short-term effect on GDP, while no significant long-term relationship exists. Moreover, excessive reliance on consumer-oriented military expenditures, coupled with weak domestic defense industries, limited Iraq’s capacity to translate security outlays into sustainable economic growth. Novelty: By applying ARDL modeling to two decades of Iraqi data, this study provides a nuanced distinction between transitory and persistent impacts of defense spending. Implications: The results suggest that fiscal policies should balance security needs with investments in productive sectors, redirecting resources toward infrastructure, education, and healthcare to foster long-term stability and growth.Highlight : Military spending in Iraq was mostly consumer, not productive. The ARDL model confirmed only a short-term impact on GDP. High defense focus reduced resources for education, health, and infrastructure. Keywords : Military Spending, GDP, Autoregressive Model, Iraq, Economic Growth